Psychological and psychiatric problems in patients with chronic pain - Doleys, Daniel M. (New York, NY : Oxford University Press, 2021)
This text presents a variety of real-life case studies encountered in the context of treating patients complaining of chronic pain. It highlights the complexity of chronic pain and its management. At times, progress can be slow and tedious, but achievable. Both clinician and patient must be clear and realistic about the therapeutic goal(s). Many of the interventions discussed are based on scientifically sound behavioral/psychological principles. However, many of these techniques can be successfully implemented by the front-line clinician.
Also issued in print: 2021.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on March 17, 2021).
Keywords: Chronic pain -- Psychological aspects; Chronic pain -- Patients -- Psychology